Dynamics with Fractals - Akhmet, Marat; Fen, Mehmet Onur; Alejaily, Ejaily Milad (Discontinuity, Nonlinearity, and Complexity, 2026)
When deterministically extended structures are taken into consideration, it is admissible that fractals are dense both in the nature and in the dynamics. In particular, this is true because fractal structures are closely related to chaos. To make advances in the direction, first of all, one should consider fractals as states of dynamics. If one realizes this approach, fractals will be proved to be dense in the universe, since modeling the real world is based on differential equations and their developments.